(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the scholarly legacy of Burhaniddin Marghinani (1123–1197), a central figure in the development of Hanafi Islamic jurisprudence and one of the most distinguished representatives of the twelfth-century scientific renaissance in Transoxiana. The study analyzes the principal works of Marghinani including “Bidayat al-Mubtadi,” “Kifayat al-Muntahi,” “Hidaya,” “Mukhtarat an-Nawazil,” and “At-Tajnis wal-Mazid” examining their structural composition, the history of their composition, their manuscript and printed tradition, and their place in the development of fiqh science. Special attention is given to the question of the volume of “Kifayat al- Muntahi,” the role of “Hidaya” in world legal civilization, and the ongoing significance of Marghinani’s heritage for contemporary Islamic scholarship and the academic tradition of Uzbekistan.